2019
DOI: 10.1002/ajpa.23974
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular variation in the first metacarpal and manipulation in hominids

Abstract: Objectives: The dexterity of fossil hominins is often inferred by assessing the comparative manual anatomy and behaviors of extant hominids, with a focus on the thumb. The aim of this study is to test whether trabecular structure is consistent with what is currently known about habitually loaded thumb postures across extant hominids.Materials and methods: We analyze first metacarpal (Mc1) subarticular trabecular architecture in humans (Homo sapiens, n = 10), bonobos (Pan paniscus, n = 10), chimpanzees (Pan tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 178 publications
(343 reference statements)
4
44
0
Order By: Relevance
“…The trabecular distribution within the finger metacarpal heads suggests A. sediba loaded its finger joints in a flexed power grip posture, similar to that of Pongo. In contrast, the internal structure of the thumb metacarpal is human-like, otherwise only showing an affinity with one Gorilla specimen, a dexterous taxon 38,46 which has the closest thumb-tofinger length ratio to humans among great apes 4 . This trabecular distribution in MH2 suggests habitual use of an abducted opposed thumb that is typical of human forceful precision grips.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The trabecular distribution within the finger metacarpal heads suggests A. sediba loaded its finger joints in a flexed power grip posture, similar to that of Pongo. In contrast, the internal structure of the thumb metacarpal is human-like, otherwise only showing an affinity with one Gorilla specimen, a dexterous taxon 38,46 which has the closest thumb-tofinger length ratio to humans among great apes 4 . This trabecular distribution in MH2 suggests habitual use of an abducted opposed thumb that is typical of human forceful precision grips.…”
Section: Discussionmentioning
confidence: 91%
“…Segmented metacarpal images were processed with the whole-epiphysis method, as described in more detail in many studies 24,26,42 and subsequent geometric morphometric landmark analysis was performed in a similar manner to that described in 46,51 . In brief, a number of image filters, run via medtool 4.2 (Dr. Pahr Ingenieurs e.U.…”
Section: Trabecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This characterization can elucidate which specific thumb movements and, by extension, which grip(s) would have been favored by this morphology; that is, would each TMc complex be better suited to precision (i.e., involvement of the pad of the fingers in opposition to the pad of the thumb) or power grips (i.e., involvement of the palm of the hand). Following previous studies of external and internal bone morphology, we predict that humans will demonstrate a TMc complex morphology that favors thumb abduction [44][45][46] as this movement, combined with axial pronation and flexion of the thumb, comprises thumb opposition. An opposed thumb is habitually used by modern humans in strong precision "pad-to-pad" grips 47 , in which the thumb pad opposes the index finger pad, and the joints of the TMc complex are oriented obliquely relative to the transverse plane.…”
mentioning
confidence: 93%
“…More recently, experimental studies have generated evidence supporting these hypotheses (e.g., the presence of an independent flexor pollicis longus muscle (Hamrick et al, 1998; Marzke et al, 1998), a robust pollical metacarpal; Rolian et al, 2011; Key & Dunmore, 2015; Williams‐Hatala et al, 2018). Still other quantitative studies have reported osteological responses to stone tool and other manual manipulative behaviors (e.g., Dunmore et al, 2020; Dunmore, Bardo, Skinner, & Kivell, 2019; Niewoehner, Weaver, & Trinkaus, 1997; Stephens, Kivell, Pahr, Hublin, & Skinner, 2018; Tocheri, Razdan, Williams, & Marzke, 2005). Based on this reasoning, we propose that the second digit, particularly the metacarpal head, should be investigated further for possible osteological signatures of habitual and skilled stone tool behaviors.…”
Section: Discussionmentioning
confidence: 99%